In Silico Repositioning Strategies of Theobromine and Caffeine for Psychiatric and Neurological Disorders - Sari, Dewi Ratih Tirto; Krisnamurti, Gabriella Chandrakirana (Proceeding International Conference on Religion, Science and Education, 2022)
Psychiatric and neurological disorders (PNDs) have correlated diseases and represent a burden on public health. Several drugs are reported to repurpose PNDs therapy. Drugs with antidepressants, anxiolytics, stimulants, antipsychotics, and mood stabilizers are classified for PNDs treatments. Due to the high cost of PNDs therapy and developing novel drugs, this study focused on identifying the theobromine and caffeine for PNDs treatments. Theobromine and caffeine as main compounds of brewed coffee and chocolate were downloaded their 3D structure from the PubChem compound database. Several targetted PNDs proteins involved Adenosine 1 receptor, adenosine 2 receptor, serotonin receptor, GABA receptor, and Acetylcholinesterase were downloaded from protein data bank and predicted their binding cavities by Molegro virtual docker 5. Ligands and proteins were docked and visualized to investigate the inhibition sites. Caffeine and theobromine showed interaction with adenosine 1 receptor and adenosine 2 receptor in adenosine sites, since there were depicting similar structure. Caffeine and theobromine also performed same active sites with serotonin receptor 4 and GABA receptor, indicating a potential activity as serotonin and GABA molecules. Acetylcholinesterase was inhibited by caffeine and theobromine at the catalytic residues. In summary, caffeine and theobromine performed a potential neuroprotection effect for PNDs therapeutics.